Impacts of urban land use and land cover changes on land surface temperature in Kuala Lumpur, Malaysia - Nur Hakimah Asnawi; Lam, Kuok Choy (Penerbit Universiti Kebangsaan Malaysia, 2024)
Urbanisation has triggered massive development activities which led to significant changes in land use and land cover (LULC). Fundamentally, the changes in LULC has to be monitored to detect the presence of regional environmental changes and impacts. Hence, this study aims to evaluate the effects of LULC changes on land surface temperature (LST) in Kuala Lumpur from 1990 to 2022 using remote sensing data. The time-series Landsat data was used to map the LULC changes, and the LST was retrieved from the Landsat thermal bands. Normalised Difference Vegetation Index (NDVI) was computed to determine its relationship with LST and LULC. The findings show more than 68% of vegetation cover in Kuala Lumpur vanished within 32 years, while the built-up land expanded by more than 50%, and water bodies dropped by more than 45%. The correlation between LST and NDVI is associated with the distribution of vegetation cover, where LST is inversely related to NDVI. A decrease in the NDVI mean value from 0.3 to 0.2 in 2022 reflected in the rise of an average mean of LST from 22.9°C to 26.2°C in 2022. A decrease in vegetation cover can contribute to the increase in surface temperature. Hence, it can be inferred that it is essential to take effective approaches in urban development planning to minimise effects on urban climate change.